Essays on the Modern Japanese Church : Christianity in Meiji Japan - Yamaji, Aizan (University of Michigan Press, 2020)
Essays on the Modern Japanese Church (Gendai Nihon kyokai shiron), published in 1906, was the first Japanese-language history of Christianity in Meiji Japan. Yamaji Aizan$1 (Bs firsthand account describes the reintroduction of Christianity to Japan$1 (Bits development, rapid expansion, and decline$1 (Band its place in the social, political, and intellectual life of the Meiji period. Yamaji$1 (Bs overall argument is that Christianity played a crucial role in shaping the growth and development of modern Japan.s
English
Keywords: Society and social sciences; Medical anthropology; Veterinary medicine: infectious diseases and therapeutics